2020
DOI: 10.1186/s12905-020-01107-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function and metabolic/hormonal changes in women using long-term hormonal and non-hormonal contraceptives: a pilot study

Abstract: Background Female sexual dysfunction is a common condition that negatively impacts the emotional health and quality of life of the affected individuals. Long-acting reversible contraceptives (LARCs) are becoming increasingly popular due to their effectiveness and convenience. LARCs can be hormonal (etonogestrel releasing implant—ENG and Levonorgestrel intrauterine system—LNG) or non-hormonal (copper intrauterine device—CuIUD and copper-silver intrauterine device—SIUD). There are very few studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Di Carlo et al [122] demonstrated that in the short term (first three months of treatment), patients experienced a temporary reduction of vitality, mental health, social functioning, and emotional role functioning; thereafter, an improvement in general health status and physical role status was observed [122]. Some data suggested a positive Nexplanon influence on sexual function (increase in pleasure, personal initiative, and orgasm) with a secondary decrease in anxiety and discomfort [101]; conversely, other authors suggest that ENG implants had a negative influence on sexual function, probably by blocking ovarian function and thus reducing the production of androgens and oestrogens [123]. A rare case of secondary etonogestrelrelated anorgasmia was described [124].…”
Section: Nexplanonmentioning
confidence: 99%
“…Di Carlo et al [122] demonstrated that in the short term (first three months of treatment), patients experienced a temporary reduction of vitality, mental health, social functioning, and emotional role functioning; thereafter, an improvement in general health status and physical role status was observed [122]. Some data suggested a positive Nexplanon influence on sexual function (increase in pleasure, personal initiative, and orgasm) with a secondary decrease in anxiety and discomfort [101]; conversely, other authors suggest that ENG implants had a negative influence on sexual function, probably by blocking ovarian function and thus reducing the production of androgens and oestrogens [123]. A rare case of secondary etonogestrelrelated anorgasmia was described [124].…”
Section: Nexplanonmentioning
confidence: 99%
“…This study has highlighted the fact that progestogen contraceptives may differ considerably and unpredictably in their effects on behaviour and menstruation and cannot be considered similar in terms of behavioural effects and effects on HIV risk. For example, the etonorgestrel implant has been associated with impaired sexual function, thought to be related to suppression of estrogen and testosterone [ 20 ], but we do not have robust data comparing this effect with other methods. Intramuscular norethisterone enanthate has many similar behavioural effects to DMPA-IM, but less glucocorticoid and immunosuppressive effects] [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…40 Etonogestrel-releasing subdermal implant (ENG-implant) ENG is a subcutaneous implant that systematically releases a synthetic substance similar to progesterone. 45 In a study evaluating the effectiveness of the ENG-implant compared to the 52-mg LNG-IUS in the control of endometriosis-related pelvic pain, both contraceptives were shown to significantly improve dysmenorrhea, pelvic pain and HRQoL. 46 Subdermal implants (ENG-implant 68 mg with a life span of 3 years) have been found to be as effective in pain relief over 12 months of use as DMPA.…”
Section: Medroxyprogesterone Acetatementioning
confidence: 99%